Draft genome sequence of Lactococcus lactis subsp. lactis bv. diacetylactis CRL264, a citratefermenting strain - Zuljan, Federico Alberto (2016)
We report the draft genome sequence of Lactococcus lactis subsp. lactis bv. diacetylactis CRL264, a natural strain isolated from artisanal cheese from northwest Argentina. L. lactis subsp. lactis bv. diacetylactis is one of the most important microorganisms used as starter culture around the world. The CRL264 strain constitutes a model microorganism in the studies on the generation of aroma compounds (diacetyl, acetoin, and 2,3-butanediol) by lactic acid bacteria. Our genome analysis shows similar genetic organization to other available genomes of L. lactis bv. diacetylactis strains.